Decaimiento Polinomial y Modelaje Numérico Computacional de la viga de Timoshenko con disipación parcial - Frank Henry Acasiete Quispe; Neisser Pino Romero (Selecciones Matemáticas, 2018)
We studied the uniform stabilization of a class of Timoshenko systems with partial dissipation of the beam. Our main result is to prove that the semigroup associated to this model has polynomial decay. Moreover, we prove that the semigroup decays polynomially to zero. The system decays polynomially with rate depending on the coeficients of the problem. We also show the computational modeling of the system showing the results obtained theoretically.